Factors influencing the occurrence of premature and excessive leaf abscission in the avocado (Persea americana Mill.) cultivar 'RYAN' and possible preventative measures - Taylor, Nicolette Jane (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2009.